The ghoul next door - Bunn, Cullen (HarperAlley, an imprint of HarperCollins Publishers, 2021)
"Eleven-year-old Grey lives in the legend-haunted New England town of Ander's Landing, and he can't help but feel like a pair of eyes is watching his every move. He discovers odd, gruesome bits and pieces from the graveyard that are left for him as gifts like art carved from bones or jewelry made from (hopefully not human) remains. Soon Grey is caught up in something bigger than he could ever have imagined. He finds himself drawn into a strange mystery involving a race of reclusive subterranean creatures--ghouls, the eaters of the dead! Turns out, his secret admirer is a ghoul named Lavinia. An unlikely friendship forms between them. The only problem is, their friendship breaks traditions--and the punishment is a fate worse than death"--Publisher's website